Prevalence and molecular characterizations of seven additional drug resistance among multidrug-resistant tuberculosis in China: A subsequent study of a national survey. Issue 3 (March 2021) - Wang, Guirong; Jiang, Guanglu; Jing, Wei; Zong, Zaojing; Yu, Xia; Chen, Suting; Li, Weimin; Huang, Hairong
Highlights: Dlm, Lzd, Cfz and Bdq exhibit excellent in vitro activity against MDR-TB, even among the most severe drug resistant pattern, XDR-TB. High resistance rate against PZA suggests to use this drug with caution. The existence of drug resistance to all the tested drugs highlighted the necessity of a timely, feasible and reliable DST for them prior to administration. Summary: The drug resistance prevalence data facilitates selection of the initial drug for treating multidrug-resistant tuberculosis (MDR-TB). The aim of this study was to investigate the prevalence and molecular characterization of seven additional types of drug resistances among MDR-TB isolates collected from the first/only nationwide drug resistance surveillance in China. A total of 391 out of the 401 MDR-TB strains were successfully recovered by Löwenstein–Jensen medium. Drug susceptibility testing was performed against moxifloxacin (Mfx), bedaquiline (Bdq), linezolid (Lzd), clofazimine (Cfz), cycloserine (Cs), delamanid (Dlm) and pyrazinamide (PZA). The strains were subjected to whole-genome sequencing for the analysis corresponding drug resistant genes and their profiles. 269 (68.80%) were simple MDR-TB, 28 (7.16%) were extensively drug-resistant tuberculosis (XDR-TB) and 94 (24.04%) were pre-XDR-TB. Dlm, Lzd, Cfz and Bdq presented the lowest drug resistant rates i.e. 3.32% (13/391), 3.84% (15/391), 6.65% (26/391) and 7.16% (28/391), respectively. Mfx (17.39%, 68/391) and CS (13.55%, 53/391) also demonstrated strong potencies against the MDR strains, whereas PZA (38.36%, 150/391) presented much higher resistant rate. 54.41% (37/68) Mfx-resistant strains carried mutations located within gyrA or gyrB . 70.15% (94/134) PZA-resistant strains had pncA mutations. Two of the 26 Cfz-resistant isolates had mutation in Rv0678 were also resistant to Bdq. Dlm, Lzd, Cfz and Bdq exhibited excellent activity against MDR-TB, including XDR-TB. These data highlighted the necessity of a timely, feasible and reliable DST, while genotypic DST for Mfx and PZA is promising at this moment.